PENGARUH PENGALAMAN FKIP EDU (EKSPLORASI EDUKASI) DAN PERSEPSI TENTANG PPG TERHADAP KESIAPAN MENJADI GURU - Sri Intan Zainatun Nisa; Ati Sadiah; Iis Aisyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research is motivated by the low readiness to become teachers in Economics Education students of the Class of 2021. The purpose of this study is to analyze the influence of FKIP EDU (Educational Exploration) experience and perception of PPG, both partially and simultaneously, on teacher readiness. This study uses a quantitative approach, a survey method, with a population of 102 Economics Education students Class of 2021. The sampling technique is nonprobability sampling, while data analysis uses parametric statistics. The results of the study show that: (1) FKIP EDU (Educational Exploration) experience has a significant effect on readiness to become a teacher; (2) Perception of PPG has a significant effect on readiness to become a teacher; (3) Simultaneously, the experience of FKIP EDU (Educational Exploration) and the perception of PPG have a significant effect on the readiness to become a teacher. This is reflected in the determination coefficient value of 0.516, which indicates that the experience of FKIP EDU (Educational Exploration) and the perception of PPG had an effect of 50.6% on the readiness to become a teacher, while the remaining 49.4% was influenced by other factors outside this study.